Narrative Review: Nano Kapsul Ekstrak Biji papaya (Carica Papaya L.) sebagai Antifertilitas - Shinta Nur Fajriyah; Yuliana Eka Lestari; Nadiatul Istiqamah Suaka; Endang Darmawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Papaya (Carica Papaya L.) is a plant commonly found in Indonesia. Interestingly, its seeds traditionally used as antifertility. All parts of the Carica Papaya tree can be used for human needs from the fruit, leaves, seeds, sap, and stems. Carica Papaya seed extract contains secondary metabolite compounds in class Triterpenoids, flavonoids, alkaloids, saponins, and tannins which have functioned as antifertility. Nanocapsule is an innovation of nanoparticle dosage form with small particle size, that can accelerate the drug to the target. This Narrative Review purposed to determine the usefulness of the nanocapsules of Carica Papaya seed extract as antifertility. This research is a Narrative Review. A total of 36 articles that met the inclusion and exclusion criteria were analyzed descriptively, which include the efficacy of Carica Papaya, nanocapsules, and antifertility. The articles used include articles published in national journals and international journals. The result of the Narrative Review is presented in descriptive form. The results of the research show that Carica Papaya can be used traditionally to treat skin diseases, diarrheal disease, overcoming digestive disorders, and by research can be used as antifertility, The size of the nanoparticles obtained in the study ranged from 76.47 nm to 693.8 nm, and Carica Papaya seed extract is used as an antifertility by reducing sperm quantity, semen pH, spermatogenesis process, interfering the action of pituitary gonads, by preclinical reducing the number of ovum quality and the number of de Graff Follicles in female mice. Overall, it can be concluded that Carica Papaya nanocapsules in particle sizes between 76.46 nm to 693.8 nm can be used as antifertility that preclinically can affect the reproduction of female and male mice.